Revisiting second language portfolio assessment in a new age. (December 2021) - Abrar-ul-Hassan, Shahid; Douglas, Dan; Turner, Jean
Abstract: As the field of L2 teaching undergoes enormous and wide-ranging developments, a "critical examination of the established assessment practices" (Hu, 2012, p. 123) seems necessary. The optimal utilization of assessment in terms of validity, consistency, and authenticity (Bachman & Palmer, 2010) depends upon numerous factors, such as educational policies, desired learning outcomes, pedagogical approaches, and available resources. L2 assessment over the last several decades has diverged in two broad approaches, traditional assessment and alternative assessment. Although traditional L2 assessment is currently widespread around the globe, there are calls for exploring alternative assessment options. Among alternative assessment possibilities, portfolio assessment emerged in the last 15 years as being valuable due to its pedagogical usefulness, leading to its use in many teaching contexts. Portfolio assessment may be particularly relevant given temporary and permanent changes to educational practices due to the emphasis on remote learning during and as a consequence of COVID-19. Portfolio assessment has undergone considerable scrutiny over the years of its use, and this paper, building on the relevant scholarship, revisits how portfolios have withstood the challenge of being a sound alternative in assessment against the backdrop of post-modernist and constructivist approaches to L2 education.